OBSERVATION ON BREAST SELF EXAMINATION (BSE) FOR EARLY DETECTION OF BREAST CANCER IN STUDENTS AT HEALTH FACULTY OF MH. THAMRIN UNIVERSITY - Rosa Susanti; Dewi Suri Damayanti (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
The prevalence of cancer had increased in the last five years. According to the Basic Health Research (Riskesdas) in 2018, the prevalence of cancer in Indonesia reaches 1.79 of 1000 population, up from 2013 as many as 1.4 of 1000 population. The study aimed to describe Breast Self Examination (BSE) for Early Detection of Breast Cancer. Study Stages (i) preparation: disseminating questionnaires through Google form, (b) identifying respondents who have done and never conducted with BSE (c) determining population (d) sampling. Stage (ii) implementation: data collection using a questionnaire and checklist. Stage (iii) Analysis bivariate with Chi-square. Respondents in this study were 100 people. The result of this study that respondents whom BSE Practice well 42% and poorly 58% and there is a significant relationship between information exposure to BSE Practice. Keywords: Behaviour, Practice, Breast Self Examination (BSE)